Hubungan Pengetahuan dan Dukungan Keluarga dengan Cara Merawat Pasien Halusinasi di Wilayah Kerja Puskesmas Kebun Handil Kota Jambi - Vevi Suryenti Putri; Rahmi Dwi Yanti (Jurnal Akademika Baiturrahim Jambi, 2021)
Schizophrenia is a disease that affects the brain and causes strange thoughts, perceptions, emotions, movements and behaviors. One of the symptoms of schizophrenia is hallucinations. Hallucinations are one of the symptoms of sensory perception disturbance experienced by mental patients. The role and duty of family health is to care for family members who are sick, the family plays an important role as a support during the recovery and rehabilitation of patients, the support provided by the family will prevent recurrence. The purpose of this study was to determine the relationship between knowledge and family support by caring for hallucination patients in the work area of Kebun Handil Health Center, Jambi City. This study used an analytical survey method with a cross sectional design which aims to determine the relationship between knowledge and family support in caring for hallucinated patients using purposive sampling technique. The total population in this study were 144 people with a total of 53 respondents. The results of this study indicate that there is a relationship between family knowledge and how to treat hallucination patients with a P-value of 0.00. There is a relationship of family support by caring for hallucinatory patients with a P - Value of 0.00. It is hoped that the family will provide free time, sufficient knowledge and extra attention in helping patients recover